2021
DOI: 10.2166/wst.2021.409
|View full text |Cite
|
Sign up to set email alerts
|

Functioned catalysts with magnetic core applied in ibuprofen degradation

Abstract: In the present work, the performance of Ag/ZnO/CoFe2O4 magnetic photocatalysts in the photocatalytic degradation of Ibuprofen (IBP) was evaluated. This study considered the use of pure Ag/ZnO (5% Ag) and also use the Ag/ZnO/CoFe2O4 magnetic catalysts containing different amounts (5, 10 and 15% wt) of cobalt ferrite (CoFe2O4). The catalysts were characterized by Scanning Electron Microscopy (SEM), X-ray diffraction (XRD) and photoacoustic Spectroscopy. To carried the photocatalytic degradation reaction, differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…The entire apparatus described was located inside a metallic photocatalysis chamber. The photodegradation of each drug was studied separately, using four different solutions with the following initial concentrations: 5 mg L −1 of ASA, 10 mg L −1 of IBU, 10 mg L −1 of PAR and 50 mg.L −1 of SA [ 10 , 11 ]. Different pH conditions were studied (3, 5, 7 or 9), and the pH of the solution was adjusted with addition of HCl or NaOH solutions.…”
Section: Methodsmentioning
confidence: 99%
“…The entire apparatus described was located inside a metallic photocatalysis chamber. The photodegradation of each drug was studied separately, using four different solutions with the following initial concentrations: 5 mg L −1 of ASA, 10 mg L −1 of IBU, 10 mg L −1 of PAR and 50 mg.L −1 of SA [ 10 , 11 ]. Different pH conditions were studied (3, 5, 7 or 9), and the pH of the solution was adjusted with addition of HCl or NaOH solutions.…”
Section: Methodsmentioning
confidence: 99%
“…Lenzi et al 323 showed that the photocatalytic degradation of ibuprofen (10 ppm) solution (pH: 7) by 0.3 g L −1 of Ag/ ZnO/CoFe 2 O 4 (5 wt%) exhibited removal efficiencies of 80% and 47% under artificial and solar radiation, respectively. These studies also confirmed the recovery and reuse of the catalyst after 3 cycles without significant loss of catalytic activity.…”
Section: Rsc Applied Interfaces Reviewmentioning
confidence: 99%
“…In view of this, several studies have been made using metal oxide and graphitic material related photocatalysts to make wastewater free from ibuprofen. 293–357…”
Section: Removal Of Pharmaceutical Components Using Different Photoca...mentioning
confidence: 99%
“…Methodi Ordinatio classified 211 articles, and the InOrdinatio value ranged from −12.79 to 579.75, when we used 10, 8, and 8 for ∆, λ, and Ω values, respectively. The main keywords that appear in the articles were: ferrite (97); magnetic (80); cobalt (65); nanoparticle (37); degradation (35); catalyst (30); photocatalysis (28); oxide (27); dye (25); CoFeO (24); heterogeneous (22); and nanocomposites (22) (Figure 1). Another relevant bibliometric analysis is about the years of publication of the more significant InOrdinatio articles, 63% of the publications are concentrated between 2019 and 2023, Figure 2a.…”
Section: Bibliometric Analysismentioning
confidence: 99%
“…Cobalt ferrite (CoFe 2 O 4 ) is one of the most relevant ferrites due to its peculiar properties, such as high physical and chemical stability [16][17][18]. This material finds application in magnetosensitive systems [19,20], removal of pollutants from water [21][22][23][24], drug delivery [25,26], and acid mine drainage treatment [27].…”
Section: Introductionmentioning
confidence: 99%